Comparison between two layer and three layer repair of episiotomy - Garag, Seetha; S. R., Chandana Murthy; S. B., Naveen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The study was done to compare the two layer episiotomy suturing and three layer episiotomy suturing with regard to time taken to suture, number of suture material required and complications at suturing site postnatally. Methods: This study was conducted in the Gynaecology and Obstetrics department of Karnataka Institute of Medical Science, Hubli, Karnataka, India from 1st March 2015 to 30th April 2015. Results: The two layered technique required lesser suture material and lesser time compared to the three layer techhnique. Conclusions: In our study two layer techniques took lesser time and lesser suture material than three layer technique.